Differential transcriptional response following glucocorticoid activation in cultured blood immune cells: a novel approach to PTSD biomarker development - Breen, Michael S.; Bierer, Linda M.; Daskalakis, Nikolaos P.; Bader, Heather N.; Makotkine, Iouri; Chattopadhyay, Mitali; Xu, Changxin; Buxbaum Grice, Ariela; Tocheva, Anna S.; Flory, Janine D.; Buxbaum, Joseph D.; Meaney, Michael J.; et al. (Translational psychiatry, 2019)
Post-traumatic stress disorder (PTSD) is a condition of stress reactivity, whose clinical manifestations are evident when patients are triggered following exposure to a traumatic event. While baseline differences in gene expression of glucocorticoid signaling and inflammatory cytokines in peripheral blood mononuclear cells (PBMCs) have been associated with PTSD, these alterations do not fully recapitulate the molecular response to physiological triggers, such as stress hormones. Therefore, it is critical to develop new techniques that will capture the dynamic transcriptional response associated with stress-activated conditions relative to baseline conditions. To achieve this goal, cultured PBMCs from combat-exposed veterans with PTSD(+) ( n = 10) and without PTSD(−) ( n = 10) were incubated with increasing concentrations (vehicle, 2.5 nM, 5 nM, 50 nM) of dexamethasone (DEX). Across diagnosis and dosage, several genes and gene networks were reliable markers of glucocorticoid stimulation (FDR < 5%), including enhanced expression of FKPB5 , VIPR1 , NR1I3 , and apoptosis-related pathways, and reduced expression of NR3C1, STAT1 , IRF1 , and related inflammatory and cellular stress-responsive pathways. Dose-dependent differential transcriptional changes in several genes were also identified between PTSD+ and PTSD−. Robust changes in expression were observed at 2.5 nM DEX in PTSD− but not PTSD+ participants; whereas, with increasing concentrations (5 nM and 50 nM), several genes were identified to be uniquely up-regulated in PTSD+ but not PTSD− participants. Collectively, these preliminary findings suggest that genome-wide gene expression profiling of DEX-stimulated PBMCs is a promising method for the exploration of the dynamic differential molecular responses to stress hormones in PTSD, and may identify novel markers of altered glucocorticoid signaling and responsivity in PTSD.